Special theme: Macroeconomic policies for inclusive sustainable development: A framework for inclusive and sustainable growth in Asia and the Pacific - Valerie Cerra (Asia-Pacific Sustainable Development Journal, 2022)
The Asia-Pacific region faces extraordinary challenges due to economic and social disparities, made worse by the COVID-19 pandemic and rising vulnerabilities caused by climate change. Addressing these challenges will require a holistic and unified plan of action for combatting these economic and social disparities. The present paper serves to outline a comprehensive and integrated inclusive growth framework and apply it to the Asia-Pacific region. It also contains a discussion of policy options for achieving inclusive and sustainable growth.